Lipid profiles of plants and soil microbial communities are shaped by soil parent material in Australian sclerophyll forests - Grace H. Liang; Orpheus M. Butler; Charles R. Warren (Plant and Soil, 2024)
Background and aims Plant and soil microbes can reduce their phosphorus (P)-requirements by replacing phospholipids with non-P containing lipids (e.g., galactolipids, sulfolipids, and betaine lipids). There have been few studies of this process in the field (i.e., in natural ecosystems); thus, it is unclear whether a similar replacement of phospholipids with non-P lipids occurs across natural gradients of soil P-availability. Methods We compared the membrane lipid profiles of plant leaves, roots, and soil microbial communities between two adjacent native Australian sclerophyll forest ecosystems—one situated on a severely P-deficient sandstone-derived soil and the other on a comparatively P-rich shale-derived soil. The herbaceous species, Lomandra longifolia, which occurred across both soils was sampled, along with two Myrtaceae tree species associated with each soil type. Results The phospholipid content of plant leaves and soil microbes was two- to three-fold greater in the shale site than the sandstone site, but non-P lipid content did not differ between sites. Conclusion Our results indicate that plants and soil microbes can have a lower investment of P into phospholipids in response to P-deficiency without a concomitant increase in non-P lipid content. Modulations in phospholipid concentration occurred across all plant- and soil microbial-associated phospholipid classes.